Design and implementation of Pharyngeal electrical Stimulation for early de-cannulation in TRACheotomized (PHAST-TRAC) stroke patients with neurogenic dysphagia: a prospective randomized single-blinded interventional study - Dziewas, Rainer; Mistry, Satish; Hamdy, Shaheen; Minnerup, Jens; Van Der Tweel, Ingeborg; Schäbitz, Wolf; Bath, Philip M.W. (SAGE Publications, 2017)
Rationale: Ongoing dysphagia in stroke patients weaned from mechanical ventilation often requires long-term tracheotomy to protect the airway from aspiration. In a recently reported single-centre pilot study, a significantly larger proportion (75%) of tracheotomized dysphagic stroke patients regained sufficient control of airway management allowing tracheotomy tube removal (decannulation) 24–72 h after pharyngeal electrical stimulation (PES) compared to controls who received standard therapy over the same time period (20%). Aim: To assess the safety and efficacy of PES in accelerating dysphagia rehabilitation and enabling decannulation of tracheotomized stroke patients. Design: International multi-centre prospective randomized controlled single-blind trial in approximately 126 ICU patients (the 90th percentile of the calculated maximum sample size). Study outcomes: Primary outcome: proportion of stroke patients considered safe for decannulation 24–72 h after PES compared to control patients who do not receive PES. Key secondary outcomes focus on: dysphagia severity, decannulation rates, decannulation rate after a repeat PES treatment in patients persistently dysphagic after an initial PES treatment, stroke severity, duration of ICU-stay, occurrence of adverse events including pneumonia and need for recannulation over 30 days or until hospital discharge (if earlier). Discussion: Dysphagia and related airway complications are reported as one of the main reasons for stroke patients remaining tracheotomized once successfully weaned from ventilation. This study will evaluate if PES can improve airway safety sufficiently enough to allow earlier tracheotomy tube removal.